A wire indent profiling system for the assessment of crosstie bond and splitting propensity - Robertson, Aaron Andrew (My University, 2025)
Concrete railroad ties represent a critical component of transportation infrastructure. A majority of concrete crossties are created from prestressed concrete, relying on the interaction between steel tendons, or strands, and the concrete to produce prestressing force in the ties. Inadequate prestressing force or splitting significantly reduces the service life or load bearing capacity of the crossties. Smooth steel tendons do not provide reserve capacity to prestressed members, as any instantiated crack cannot be arrested; therefore, indentations are added to the steel tendons to provide reserve capacity and reduce the distance over which the prestressing force is transferred from the steel tendon to the concrete, defined as the transfer length. The geometry of these indented features significantly impacts the transfer length and splitting propensity of manufactured concrete railroad ties. Indentation geometry has been shown to have a direct influence on the performance of prestressed members. Thus, it is important to measure critical indent features to ensure that indents are being formed to the right tolerances and provide the desired wire-concrete performance. However, the measurement of such features has proven challenging in practice. Certain standards, namely ASTM A881, outline indent features to measure for quality control for wires of a given size, but fall short of describing how or where measurements will be performed. Such measurements are often done manually, suffer from poor accuracy, and are time consuming. The time-consuming nature of the measurements makes it impractical to sample enough indents to adequately statistically characterize the manufacturing process. Most importantly, the current standards do not identify which features, or combinations of features, contribute to, or reduce, wire-concrete bond performance. It is possible for indented wires to pass the requirements of the measurement standards but fail to produce desirable wire-concrete performance; this is often only discovered after the crossties have been manufactured. This research addresses the shortcomings of the current measurement standards, identifies which indent features most significantly contribute to wire-concrete performance, and outlines the development of an Indent Profiling System that is capable of extracting all important indent features. An automated, high resolution, non-contact measurement system was created and used to measure dozens of wires from modern industry, historical crossties, and lab specimens with well-defined geometry. This system measures all unique indents formed by a complete revolution of the indent rollers, providing statistically relevant sample sizes that were previously impossible using manual measurements. To identify which wire features, or combinations of features, correlate strongly with performance hundreds of prestressed prisms were created as part of a larger FRA project titled “Developing Qualification Tests to Ensure Proper Selection and Interaction of Pretensioned Concrete Railroad Tie Materials”. These prisms used the same wires that were scanned by the Indent Profiling System and were created with a variety of concrete covers, release strengths, and aggregates to assess wire-concrete performance. The known indent geometry provided by the Indent Profiling System was successfully used in conjunction with the prism tests to identify how geometry influences factors such as transfer length and splitting propensity. Lastly, a new ASTM measurement standard was proposed titled Standard Practice for Measuring Indented Steel Wire Geometrical Parameters, providing guidance on how the most important indent features are to be measured, using automated or manual methods, so that results can be repeatable from individual-to-individual or from lab-to-lab. The application of this research will help ensure that poor wire-concrete performance is identified prior to production.
Keywords: Concrete railroad ties; Prestressing steel reinforcement wire; Non-contact 3D scanning and inspection; Geometrical dimensioning and tolerancing; Quality control; Indent profiling system